MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA DINI 5-6 TAHUN (Studi tentang Pra dan Post Penerapan Metode Labatu di Kelompok Bermain Santo Vincentius A Paulo Kupang) - Lestari, Anastasia Yani; Nehung, Yupilia Saputri; Dau, Yoseph Lodowik Deki (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2024)
This research aims to evaluate children's language abilities before and after implementing the Labatu method, identify supporting and inhibiting factors, and measure the effectiveness of the method. This research uses a qualitative method with a descriptive approach to describe the influence of the Labatu method in improving the language skills of young children aged 5-6 years in the Santo Vincentius A Paulo Kupang Playgroup. Data collection techniques include observation, interviews, and documentation, and data analysis. The research results showed that before implementing the Labatu method, children experienced limited vocabulary, difficulty in forming sentences, and low understanding of expressive and receptive language. On the other hand, after effectively implementing the Labatu method, it was proven that children's language skills had significantly increased in terms of vocabulary, speaking ability and understanding of instructions. This method is considered to really support holistic learning, creating a pleasant learning environment and encouraging social interaction as well as the active role of parents and teachers in supporting the language development of children aged 5-6 years at the Santo Vincentius A Paulo Kupang Playgroup.